Numerical Investigation of Electrospray Working Performance on Ethanol - Andam Refino; Hadi Teguh Yudistira; Denny H. T. Nugroho; Deska L. Puspitarum (Journal of Science and Applicative Technology, 2019)
Electrospray as an alternative method to fabricate thin film is studied. High voltage is required by the electrospray system. The requirement of high voltage is different for various liquid depending on the surface tension property. Ethanol was used to resemble the solvent used in thin film deposition. From the experimental work, jetting performance did not occur despite of the high applied voltage which is around 1 KV. In this work, numerical calculation is carried out to find the reason behind of unsuccessful jetting at 1 KV applied voltage. The percentage of Rayleigh limit is around 0.4. Electrospray performance at walking distance 5 mm using ethanol is predicted to be stable when the applied high voltage is approximately 1.1 KV. The numerical investigation indicates that the jetting performance will occur if the applied voltage is more than 1.1 KV.